The 980-nm diode laser for brain surgery: histopathology and recovery period - (:unkn) unknown (SPRINGER LONDON LTD, 2004)
The 980-nm diode laser has been under investigation for neurosurgery because of a local peak in the absorption spectra of water around this wavelength. This work was carried out to examine the extent of thermal changes and the recovery process of laser-induced brain lesions. In order to study the quality of the lesions, a conventional monopolar electrocoagulation technique was applied comparatively. An in vivo stereotaxic neurosurgical procedure was performed on Wistar rats. Bilateral brain lesions of the same size (2-3 mm diameter) were created with a diode laser and via electrocoagulation. Subjects were sacrificed 0, 2 and 7 days after surgery in order to observe the healing process of the necrotic tissue. The surgical after-effects of both types of lesions were identified through immunohistochemical staining with CD68 macrophage marker and haematoxylin eosin (H&E). CD68 was found to be more efficient than H&E in determining the thermally altered areas. Histological examinations showed that the 980-nm diode laser system has a remarkable ablating ability with minimal thermal damage of nearby tissue.
Keywords: 980-nm diode laser; electrocoagulation; neurosurgery; photocoagulation; surgical after-effects; TISSUE; RATS; NEUROSURGERY; EXPERIENCE; ABLATION; LESIONS